Advances in damage mechanics : metals and metal matrix composites with an introduction to fabric tensors - Voyiadjis, George Z., 1946- (Elsevier, 2006)
The book presents the principles of Damage Mechanics along with the latest research findings. Both isotropic and anisotropic damage mechanisms are presented. Various damage models are presented coupled with elastic and elasto-plastic behavior. The book includes two chapters that are solely dedicated to experimental investigations conducted by the authors. In its last chapter, the book presents experimental data for damage in composite materials that appear in the literature for the first time. Systematic treatment of damage mechanics in composite materials Includes special and advanced topics Includes basic principles of damage mechanics Includes new experimental data that appears in print for the first time Covers both metals and metal matrix composite materials Includes new chapters on fabric tensors Second edition includes four new chapters.